Desafios e possibilidades na sala de recursos multifuncional para alunos com altas habilidades/superdotação - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Students with Giftedness/Talentedness (GT) are considered subjects of Special Education and require Specialized Educational Service (SES). The invisibility surrounding GT generates demands for teacher training in the pedagogical practice of teachers working in this context. This dissertation aims to investigate theoretical and practical resources that contribute to the teacher's role in the Multifunctional Resource Room for students with giftedness/talented students and systematize them into a teacher training course. The general objective of this dissertation is to investigate theoretical-practical subsidies that contribute to the teacher's performance in the Multifunctional Resource Room of students with high abilities/giftedness and to systematize them in a teacher training course. The methodological approach used was translational research in education, which seeks to foster the understanding of practice through theory and reapply knowledge by developing the teacher training course intended for pedagogical practice. The locus of the study was a municipal school in a town west of Paraná. The sample consisted of 15 teachers, 13 female and 2 male, from Basic Education, working in SES in MRR. Qualitative analysis of the data and indicators obtained from the literature review was conducted, with theoretical grounding in Renzulli (2004, 2008, 2018), in documentary analysis considering public policies on the inclusion of these students from 1961 to 2023, in normative documents guiding teaching activities in MRR in Paraná, in the development of a teacher training course as an Educational Resource (ER), and in responses to surveys on demand collection and course validation. Based on the collected educational demands, indicators were obtained to develop an ER, a free course in Distance Education modality, which supports inclusive pedagogical practice and guides teacher training for the SES context in MRR GT. The evaluation of the ER indicated contributions to the continuous training of teachers for pedagogical work in SES, which meets the actual needs of students enrolled in MRR GT. The evaluation resulted in an index of 4.86 (excellent) on a Likert scale from 1 to 5 as a general quality indicator of the developed ER. The results highlight the importance of translational research, as it allowed the transfer of scientific knowledge into applicable knowledge through the development of the ER. The research enabled, based on the utilized reference framework, the identification of inclusive strategies using the Individualized Educational Plan - IEP (Brazil, 2023) and the Triadic Enrichment Model (Renzulli 2004, 2014). Through documentary analysis, it was found that Public Policies largely address the educational needs of students with GT, but there is a recorded need for means to implement them.
Keywords: Altas Habilidades/Superdotação; Formação continuada de professores; Sala de Recursos Multifuncionais; Educação Especial Inclusiva; Giftedness/Talented Students; Continuing Teacher Education; Multifunctional Resource Room; Inclusive Special Education; CNPQ::CIENCIAS HUMANAS::EDUCAÇÃO